Marketing assistance for instant herbal drink products in the KBU Sehat home industry group, Banjar Regency - Isnaini, Isnaini; Asnawati, Asnawati; Yuliani, Rahma (Community Empowerment, 2025)
The PKK (Family Welfare Movement) mothers of KBU Village have been producing an instant herbal drink named "WIRAS" herbal medicine. For over six months of production, the sales volume has remained relatively low, with a monthly turnover of approximately IDR 375,000. This low sales turnover is primarily due to marketing and sales being conducted only on a local scale. Furthermore, the produced items lack home industry permits (P-IRT), which causes them to be considered illegal for sale. This activity aims to provide assistance in obtaining permits and improving managerial systems related to marketing, enabling wider product distribution both offline (direct sales) and online (digital marketing). The methods employed include assisting with business permit applications, marketing training, and guidance in creating social media and marketplace accounts. The outcomes of this activity are the issuance of P-IRT for the products and an increase in monthly turnover from IDR 375,000 to IDR 1,815,000.